Spacecraft and Instrument Photoelectrons Measured by the Dual Electron Spectrometers on MMS. Issue 11 (26th November 2017) - Gershman, Daniel J.; Avanov, Levon A.; Boardsen, Scott A.; Dorelli, John C.; Gliese, Ulrik; Barrie, Alexander C.; Schiff, Conrad; Paterson, William R.; Torbert, Roy B.; Giles, Barbara L.; Pollock, Craig J.
Abstract: Secondary electrons are continuously generated via photoemission from sunlit spacecraft and instrument surfaces. These particles can subsequently contaminate low‐energy channels of electron sensors. Spacecraft photoelectrons are measured at energies below that of a positive spacecraft potential and can be removed at the expense of energy resolution. However, fluxes of photoelectrons generated inside electron instruments are independent of spacecraft potential and must be fully characterized in order to correct electron data. Here we present observations of spacecraft and instrument photoelectron populations measured with the Dual Electron Spectrometers (DES) on NASA's Magnetospheric Multiscale (MMS) mission. We leverage observations from Earth's nightside plasma sheet taken during MMS commissioning and develop an empirical model of instrument photoelectrons. This model is used with DES velocity distribution functions to correct plasma moments and has been made publicly available on the MMS science data center for use by the scientific community. Key Points: Photoelectrons can contaminate low‐energy electron measurements on NASA's Magnetospheric Multiscale (MMS) mission Photoelectrons generated inside the Dual Electron Spectrometers (DES) on MMS are independent of spacecraft potential Empirical modeling of DES instrument photoelectrons can be used to correct electron distribution functions and plasma moments